Analisis Komponen Produk Wisata Di Kabupaten Karawang - Kartika, Dewi Gita; Rahmanita, Myrza (Jurnal Ilmiah Pariwisata, 2017)
Karawang Regency is one of the regencies in West Java with many tourism potentials and on the forth rank as the most visited regency to the tourism attraction by tourists in 2015. However, there found some concerns that complained by tourists, both from the bad infrastructure, potholes, the lack of facilities, less well-maintained attractions and so on. Based on the tourist’s complaints, then drawn a formulation of the problem that leads to tourism products with the five main components, such as attractions, facilities in tourist destinations, accessibility, image of destination and price for tourists with the aim of knowing how tourism products in Karawang Regency itself and which aspects that become its advantages and disadvantages. The research was conducted on 100 respondents with non-probability sampling method. Respondents should have been traveled to Karawang Regency at least once. Data were collected through questionnaires and analyzed with quantitative descriptive terms. The result of research shows that tourism product in Karawang Regency is good enough with mean 2,833, however there are some aspects that very weak and require special attention, especially on accessibility component with the lowest mean 2,542.